A national system for monitoring the performance of hospitals in Ethiopia - Zahirah McNatt; Erika Linnander; Abraham Endeshaw; Dawit Tatek; David Conteh; Elizabeth H Bradley (The World Health Organization, 2015)
Abstract Many countries struggle to develop and implement strategies to monitor hospitals nationally. The challenge is particularly acute in low-income countries where resources for measurement and reporting are scarce. We examined the experience of developing and implementing a national system for monitoring the performance of 130 government hospitals in Ethiopia. Using participatory observation, we found that the monitoring system resulted in more consistent hospital reporting of performance data to regional health bureaus and the federal government, increased transparency about hospital performance and the development of multiple quality-improvement projects. The development and implementation of the system, which required technical and political investment and support, would not have been possible without strong hospital-level management capacity. Thorough assessment of the health sector's readiness to change and desire to prioritize hospital quality can be helpful in the early stages of design and implementation. This assessment may include interviews with key informants, collection of data about health facilities and human resources and discussion with academic partners. Aligning partners and donors with the government's vision for quality improvement can enhance acceptability and political support. Such alignment can enable resources to be focused strategically towards one national effort - rather than be diluted across dozens of potentially competing projects. Initial stages benefit from having modest goals and the flexibility for continuous modification and improvement, through active engagement with all stakeholders.